Reid's doxastic theory of perception - Quilty-Dunn, J (Michigan Publishing, 2019)
Reid endorsed a doxastic theory of perception, on which beliefs are constituents of perceptual experiences. This theory faces the problem of known illusions: we can perceive that p while believing that not-p. Some scholars argue that the problem of known illusions and other problems entail that Reid’s view cannot be charitably interpreted as a doxastic theory. This paper explores Reid’s theoretical commitments with respect to belief acquisition and uses textual evidence to show that his theory is genuinely doxastic. It then argues that a Reidian response to the problem of known illusions can be formulated by appeal to the thesis that perceptual beliefs are formed noninferentially. Reid can also resist the intuition that we lack illusory beliefs in known-illusion cases given his independent reasons for doubting our capacity to identify perceptual beliefs by introspection. The paper then surveys other problems raised in the secondary literature and argues that none decisively undermine the doxastic interpretation of Reid.